Medicolegal Injury Report Writing: Lessons to be Learnt by Doctors: A Case Report (Indian Internet Journal of Forensic Medicine and Toxicology, 2020)
A petition was filed before Punjab and Haryana High Court by a doctor for quashing of the order of suspension dated 18.6.1993 by which the petitioner (Doctor) was dismissed from service on the ground that it has been found that he was guilty of changing the Medico Legal Report and tampering with it and thus having conducted himself irresponsibly, while on Government duty. It was contended that the mistake in the Medico Legal Report was a result of inexperience being his first posting on permanent basis, therefore, the order of the dismissal was not justified and that he was only a Medical Officer whereas the Resident Medical Officer was to prepare the Medico Legal Report but was on leave on that date and, therefore, the petitioner could not be held responsible. This paper deals with issues related to preparation of Medicolegal Injury report, lapses in report, tempering of injury report, not mention of weapon, cutting, over writing etc. and its impact on outcome of case i.e. acquittal of alleged accused. Power of Disciplinary Authority and relevant case laws has been discussed in brief. What are legal consequences of tempering and inadequacies in preparing medico legal reports? Aim of this research paper is to create awareness among young doctors about their role in preparing a legal document /report and to avoid legal action against them by taking all precautions.
Keywords: Medicolegal injury report; Tempering; Misconduct; Disciplinary authority